Nitrous oxide emission estimation from managed soils in Argentina : differences between IPCC 2006 guidelines and the IPCC 2019 refinement - Said, Andrés (2022)
Fil: Said, Andrés. Universidad de Buenos Aires. Facultad de Agronomía. Buenos Aires, Argentina.